(3OjhGf GdjhSjs - (3GdMSf Hf eSYhO Hf eMeO, CHh Ydj, fhQ GdOjf GdjhSj,J (B1102 (3g` s
(3ChdgG (B:s
(3Ef Hjf GdZeGe hGdRgQ GdZrV` V doQnMei bOjeI hENGA s
(3BNQgG (B:s
(3hef ShGge ef ShGO GdeUdjf hGdMeO ddg QH GdYGdejf s
(3jdj GdOjhGf CQLhRI aj GdabIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B251 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(79 (3O(B) s
Keywords: (3GdCOHs